Mental health problems and associated factors of students at different learning stages during and after COVID-19 pandemic in Sichuan, China - Jia Cai; Yu Wang; Cong Wang; Zhong-Yue Deng; Yun-Fei Mu; Ai-Ping Deng; Hong-Jun Song; Yi Huang; Ding-Zhi Fang; Ge-Lin Liu; Yan Hu; Xin Yang; et al. (BMC Psychiatry)
Abstract Background Although students’ mental health might be impacted severely during the COVID-19 pandemic, there is still limited clarity regarding mental health problems among students in different learning stages after the lifting of COVID-19 restrictions in China. This study aimed to explore the long-term effects of COVID-19 on students’ mental health at different learning stage and provide recommendations on education and health policies after the lifting of COVID-19 constrictions. Method This large sample, cross-sectional, online survey was conducted among students (N = 82873) in 162 schools from December 14, 2022 to February 28, 2023 in Sichuan, China. The online self-report questionnaires were sent firstly to school teachers or professors, then these teachers or professors sent the questionnaires directly to their students at schools. The scales included the Chinese version of 9-item Patient Health Questionnaire-9 (PHQ-9), the Generalized Anxiety Disorder-7 (GAD-7), the Insomnia Severity Index (ISI), the PTSD Checklist for DSM-5 (PCL-5). All the mentioned instruments showed satisfactory reliability and validity. Results The prevalence of depression symptom in middle school group, high school group and college group was 28.5%, 45.0%, 37.3%, the anxiety symptom was 24.0%, 38.4%, 29.7% and the PTSD was 25.7%, 40.6%, 32.1%, respectively. Among the 3 groups, the high school group had the highest rate of depression symptom (45.0%), anxiety symptom (38.4%), PTSD (40.6%), insomnia (39.9%) and lifetime suicidal ideation (28.9%). For all the three groups, there were same factors increased the risk of depression and anxiety symptoms, such as academy dissatisfaction, higher score of Internet Addiction Test (IAT), ISI, cyberbullying and traditional bullying et al., while higher score of Social Support Rating Scale (SSRS) decreased the risk. In addition, each group had unique risk factors for depression and anxiety symptoms. Conclusion This study revealed that students at different learning stage were still experiencing serious mental health problem even after the lifting of COVID-19 restrictions in China. Special attention should be paid to the mental health of students, especially high school students. Education and health policies and psychosocial interventions should be developed according to the characteristics and various influencing factors of students at different learning stages.